4-Octyl itaconate reduces influenza A replication by targeting the nuclear export protein CRM1 - O'Neill, Luke (My University, 2023)
In recent years, especially since the outbreak of the severe acute respiratory syndrome coronavirus 2 pandemic, the cell-permeable itaconate derivative 4-octyl itaconate (4-OI) has gained traction as a potential antiviral agent. Here, we demonstrate that 4-OI inhibits replication of multiple influenza A viruses (IAV) by restricting nuclear export of viral ribonucleoproteins, a key step in the IAV replication cycle. This nuclear retention is achieved by deactivation and subsequent degradation of chromosomal maintenance 1 protein (CRM1), also known as exportin 1 (XPO1), a host cell protein exploited by IAV during replication. 4-OI-mediated deactivation of CRM1 resulted in the accumulation of the IAV nucleoprotein, the Rev protein of feline immunodeficiency virus, as well as the natural CRM1 cargos p53 and p65, in the nucleus of treated cells. Further mechanism of action studies revealed that, similar to known CRM1 inhibitors, 4-OI modifies a key cysteine in the cargo binding pocket of CRM1 at position 528 through an alkylation reaction called 2,3-dicarboxypropylation. Subsequent studies in a cell line in which the cysteine at position 528 in CRM1 protein was substituted by a serine confirmed that modification of this residue was indeed the cause for the observed inhibitory effect induced by 4-OI on CRM1 function. Overall, this study demonstrated a mechanism through which 4-OI directly interferes with the replication cycle of CRM1-dependent viruses, which contributes to the understanding of the antiviral and anti-inflammatory properties of this multifaceted immuno-metabolite. IMPORTANCE Itaconate derivates, as well as the naturally produced metabolite, have been proposed as antivirals against influenza virus. Here, the mechanism behind the antiviral effects of exogenous 4-octyl itaconate (4-OI), a derivative of itaconate, against the influenza A virus replication is demonstrated. The data indicate that 4-OI targets the cysteine at position 528 of the CRM1 protein, resulting in inhibition of the nuclear export of viral ribonucleoprotein complexes in a similar manner as previously described for other selective inhibitors of nuclear export. These results postulate a mechanism not observed before for this immuno-metabolite derivative. This knowledge is helpful for the development of derivatives of 4-OI as potential antiviral and anti-inflammatory therapeutics.
PUBLISHED
Keywords: severe acute respiratory syndrome coronavirus 2; pandemic; derivative 4-octyl itaconate (4-OI); influenza virus, CRM1, itaconate, 4-OI, antiviral; severe acute respiratory syndrome coronavirus 2; pandemic; derivative 4-octyl itaconate (4-OI)